Strategi Komunikasi Interpersonal Guru Dalam Penguatan Pendidikan Karakter Siswa di SMA Swasta Kartika I-1 Medan - Muhammad Fadli Ashari (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2026)
The success of character development is closely related to teachers' interpersonal communication strategies in establishing effective relationships with students. This study aims to analyze teachers' interpersonal communication strategies in strengthening students' character education at SMA Swasta Kartika I-1 Medan. This research employed a descriptive qualitative approach. Data were collected through in-depth interviews, observations, and documentation involving three informants, namely the vice principal for curriculum affairs, the vice principal, and the guidance and counseling teacher. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings revealed that teachers implemented interpersonal communication strategies through five dimensions: openness, empathy, supportiveness, positiveness, and equality. These dimensions fostered harmonious relationships, enhanced students' trust in teachers, and created effective communication in the character-building process. Furthermore, the implementation of these interpersonal communication strategies contributed to strengthening students' discipline, responsibility, and mutual respect. Therefore, teachers' interpersonal communication plays a significant role in supporting the successful implementation of character education at SMA Swasta Kartika I-1 Medan.